2003
DOI: 10.1002/jccs.200300044
|View full text |Cite
|
Sign up to set email alerts
|

New Triterpenoid Fatty Acid Esters from the Small Twigs of Viburnum Odoratissimum

Abstract: α‐Amyrin margarate (1), moretenyl margarate (2) and moretenyl palmitate (3), three triterpenoid fatty acid esters, have been isolated from the acetone extract of the small twigs of Viburnum odoratissimum in addition to the three known compounds, α‐amyrin palmitate (4), ursolic acid (7) and vibsanin‐K (8). The structures of compounds 1–3 were elucidated based on extensive spectroscopic analysis and alkaline hydrolysis. Preliminary pharmacological studies revealed that vibsanin‐K and ursolic acid exhibited signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Its molecular formula was deduced to be C 48 H 78 O 18 from the HRESI-MS (m/z 941.5121, [M−H] − ; calcd. for 941.5110) and confirmed by 13 C NMR and DEPT spectra ( Table 1). The IR spectrum showed absorptions for hydroxyl (3440, 3426 cm -1 ), carbonyl (1682 cm -1 ) and glycosidic C─O (1068, 1043 cm -1 ) groups.…”
mentioning
confidence: 62%
See 2 more Smart Citations
“…Its molecular formula was deduced to be C 48 H 78 O 18 from the HRESI-MS (m/z 941.5121, [M−H] − ; calcd. for 941.5110) and confirmed by 13 C NMR and DEPT spectra ( Table 1). The IR spectrum showed absorptions for hydroxyl (3440, 3426 cm -1 ), carbonyl (1682 cm -1 ) and glycosidic C─O (1068, 1043 cm -1 ) groups.…”
mentioning
confidence: 62%
“…In our previous studies, some Gelsemium alkaloids with either anticancer or immunosuppressive activity have been reported from the stems and leaves of G. elegans [4]. Herein we report the isolation from the stems and leaves of G. elegans and structural elucidation of a new triterpenoid saponin, odoratanone A (1) together with twelve known compounds 2--D-glucopyranosyloxy-5-methoxy methyl benzoate (2) [5], paeonol (3) [6], ethyl vanillate (4) [7], ethyl caffeate (5) [8], stigmastane-3,6-dione (6) [9], β-sitosterol (7), β-daucosterol (8), 24-hydroperoxy-24-vinylcholesterol (9) [10], lupeol (10) [11], α-amyrin (11) [12], ursolic acid (12) [12], α-amyrin margarate (13) [13], and a mixture of cerebrosides (14) [14].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[70] The leaves of Viburnum awabuki afforded two vibsane hydroperoxides vibsanin K (51) and 18-Omethylvibsanin K (52) of which vibsanin K exhibited significant cytotoxicity against human gastric and oral epidermoid tumor cells at a concentration of 50 μg/mL. [71][72][73] According to the data given in this article, plants synthesize mainly DHs (51 of 94). Data on the biological activity of hydroperoxides are given in tables 1-3.…”
Section: Diterpenoid Hydroperoxides (Dh) Derived From Liverworts and mentioning
confidence: 98%
“…Surprisingly, there was no HMBC correlation between proton H-3 and the carbonyl group of the fatty acid at δ C 179.7 (C-1′). The fact that the chemical shift of this proton at δ H 3.48 was unusually shielded in comparison to acylated oleanane triterpenes at H-3 position, which are observed between δ H 4.46-4.57 [12][13][14][15][16], indicated that the ester moiety of the fatty acid was not located at C-3 position. In view of these observations, the only available position for the fatty acid chain previously stated, would be at the isopropylienedioxy carbon (C-1") attached to C-23.…”
Section: Structure Elucidation Of Isolated Compoundsmentioning
confidence: 99%